OCEANOGRAPHIC DATA OF THE 23RD JAPANESE ANTARCTIC RESEARCH EXPEDITION FROM NOVEMBER 1981 TO APRIL 1982 - オカ, カツジロウ; フチノエ, セイジ; OKA, Katsujiro; FUCHINOUE, Seiji (National Institute of Polar Research, 1984)
P(論文) This report presents the data of the oceanographic observations made on board the icebreaker Fuji and the tidal observation at Syowa Station, which were carried out in the summer mission of the 23rd Japanese Antarctic Research Expedition in 1981-1982. departmental bulletin paper